Atlantis, the lost empire ; Atlantis, Milo's return [videorecording (Blu-Ray + DVD)] - Garner, James; Fox, Michael J., 1961-; Nimoy, Leonard; Varney, Jim; Mahoney, John, 1940-2018; Summer, Cree; Brown, Clancy; Taylor, James Arnold, 1969- (Disney Blu-ray., 2013)
Atlantis: the Lost Empire: A young adventurer named Milo Thatch joins an intrepid group of explorers to find the mysterious lost continent of Atlantis. Milo's Return: Milo and Kida reunite with their friends to investigate strange occurrences around the world that seem to have links to the secrets of Atlantis.